An eye-tracking study on the effect of infographic structures on viewer's comprehension and cognitive load. (July 2018) - Majooni, Azam; Masood, Mona; Akhavan, Amir
The basic premise of this research is investigating the effect of layout on the comprehension and cognitive load of the viewers in the information graphics. The term 'Layout' refers to the arrangement and organization of the visual and textual elements in a graphical design. The experiment conducted in this study is designed based on two stories and each one of these stories is presented with two different layouts. During the experiment, eye-tracking devices are applied to collect the gaze data including the eye movement data and pupil diameter fluctuation. In the research on the modification of the layouts, contents of each story are narrated using identical visual and textual elements. The analysis of eye-tracking data provides quantitative evidence concerning the change of layout in each story and its effect on the comprehension of participants and variation of their cognitive load. In conclusion, it can be claimed that the comprehension from the zigzag form of the layout was higher with a less imposed cognitive load.